Effect of UDP-Glucuronosyltransferase (UGT) 1A Polymorphism (rs8330 and rs10929303) on Glucuronidation Status of Acetaminophen - Huma Mehboob; Imtiaz Mahmood Tahir; Tahira Iqbal; Sadaf Saleem; Sofia Perveen; Aboubakker Farooqi (SAGE Publishing, 2017)
Interindividual variability in polymorphic uridine diphosphate-glucuronosyltransferase 1A1 (UGT1A1) ascribed to genetic diversity is associated with relative glucuronidation level among individuals. The present research was aimed to study the effect of 2 important single nucleotide polymorphisms (SNPs; rs8330 and rs10929303) of UGT1A1 gene on glucuronidation status of acetaminophen in healthy volunteers (n = 109). Among enrolled volunteers, 54.13% were male (n = 59) and 45.87% were female (n = 50). The in vivo activity of UGT1A1 was investigated by high-performance liquid chromatography-based analysis of glucuronidation status (ie, acetaminophen and acetaminophen glucuronide) in human volunteers after oral intake of a single dose (1000 mg) of acetaminophen. The TaqMan SNP genotyping assay was used for UGT1A1 genotyping. The wild-type genotype (C/C) was observed the most frequent one for both SNPs (rs8330 and rs10929303) and associated with fast glucuronidator phenotypes. The distribution of variant genotype (G/G) for SNP rs8330 was observed in 5% of male and 8% of the female population; however, for SNP rs10929303, the G/G genotype was found in 8% of both genders. A trimodal distribution (fast, intermediate, and slow) based on phenotypes was observed. Among the male participants, the glucuronidation phenotypes were observed as 7% slow, 37% intermediate, and 56% fast glucuronidators; however, these findings for the females were slightly different as 8%, 32%, and 60% respectively. The k-statistics revealed a compelling evidence for good concordance between phenotype and genotype with a k value of 1.00 for SNP rs8330 and 0.966 for SNP rs10929303 in our population.